The Economic Impact of Pesantren Haul Traditions on Local MSME Income: Evidence from Gentur Cianjur, Indonesia - Diansyah Permana; Luqman Al-Hakim Musthafa; Ceceng Saepulmilah; Mamat Rahmat; Alfa Rohmatin; Andewi Suhartini (LP2M IAIN Palopo, 2025)
This study aims to analyze the effect of pesantren haul traditions on the income growth of local micro, small, and medium enterprises (MSMEs), with a case focus on Pesantren Gentur in Cianjur Regency, Indonesia. The haul tradition is viewed not only as a religious activity but also as a socio-economic phenomenon that has a significant impact on the surrounding community. A quantitative approach with an explanatory design was employed. Primary data were collected through surveys and interviews with 111 MSME actors around Pesantren Gentur and analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) with SmartPLS software. The results reveal that the pesantren haul tradition has a positive and significant effect on MSME income growth, with a path coefficient of β = 0.843, T-statistic = 27.710, and p < 0.001. The structural model explains 71% of the variance in MSME income growth with a substantial effect size (f² = 2.451) and strong predictive relevance (Q² = 0.593). These findings confirm that pesantren haul functions not only as a spiritual event but also as a local economic driver. The implications suggest that better management of haul traditions is essential to optimize economic benefits for MSMEs without diminishing their religious values. Local governments and pesantren managers are expected to synergize in supporting infrastructure, event governance, and MSME empowerment. Future studies are recommended to expand the scope to pesantren in other regions and to integrate variables such as MSME digitalization to enrich the analysis of religious tradition-based economic development.